divide x3-x2-(2+√2)x+√2 by x+1
Answers
Answered by
4
Step-by-step explanation:
Hey dear!!
Here's your answer
===================>
x^3-x^2-(2+√2)x+√2, here the value of 'x' is (-1)7
x
3
−x
2
−(2+
2
)x+
2
=(−1)
3
−(−1)
2
−(2+
2
)(−1)+
2
=(−1)−(+1)−2×(−1)−
2
×(−1)+
2
=−1−1+2+
2
+
2
=2
2
Attachments:
![](https://hi-static.z-dn.net/files/d21/a582c237eff6d1771c256a65d85170e1.jpg)
![](https://hi-static.z-dn.net/files/d3f/3a73d5d4fbf3cf4dd6da8eaf4fce72b8.jpg)
Similar questions
English,
5 months ago
Hindi,
5 months ago
Math,
5 months ago
Social Sciences,
10 months ago
Math,
10 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Science,
1 year ago